Affect and between-meal snacking in daily life: the moderating role of gender and age. Issue 4 (3rd April 2018) - Wouters, Saskia; Jacobs, Nele; Duif, Mira; Lechner, Lilian; Thewissen, Viviane
Abstract : Objective: Affect-related energy intake from snacks remains relatively unexplored in daily life. This study examines the associations between momentary positive affect (PA) and momentary negative affect (NA) and subsequent energy intake from snacks. In addition, the moderating role of BMI, gender, age and level of education is investigated. Design: Adults ( N = 269), aged 20–50, participated in this study. Demographics were assessed in an online composite questionnaire. An experience sampling smartphone application was used to map momentary NA/PA and energy intake (kilocalories) from snacks in the context of daily life. Main outcome measures: Energy intake from moment-to-moment self-reported snacks in real-life settings. Results: A significant negative main effect of momentary NA on moment-to-moment energy intake was found. The higher the momentary NA, the lower the subsequent amount of kilocalories consumed. There was no main effect with regard to PA. Interaction analyses showed that men decreased their energy intake after experiencing NA, and increased their intake after experiencing PA. No associations were found in women. Additionally, young adults (20–30) increased their energy intake after experiencing PA. No associations were found in the other age groups. Conclusion: Interventions aiming at reducing energy intake might also address PA-related snacking in young adults and men.